Physical properties and photocatalytic degradation studies of chlorinated hydrocarbons using TiO2 based thin films [compact disc] - 466255 Ng, Sook Chuin (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2005